(untitled) - How, Alan (New York, 2003)
This book examines the intellectual contribution made by Frankfurt School Critical Theory to our understanding of modern life. Thematically organized and offering a strong mix of historical and contemporary material, it considers the work of both the first and second generation. While the work of the latter is often taken to exceed that of the former, the author suggests that insights gleaned by both, regarding the human subject, offer a significant alternative to postmodern ideas.
Keywords: Habermas, Jürgen,Critical theory